Development of compact antenna for RFID application - Diblawe, Abdulkadir Mukhtar (2019)
In recent years, microstrip antennas have met commercial requirements. The advent of wireless applications requires a compact antenna, easy to manufacture. The goal of the project is to develop a microstrip monopole antenna for RFID tag applications that reduce size. The purpose of this antenna is to operate at 2.4 GHz. Due to its low-profile, a microstrip monopole antenna was chosen as a design model for the project.CST Microwave studio 2015 has been used to simulate the design of antennas for preliminary design purposes. This can be recognized as being unique to the advantages of the antenna. . The proposed antenna was etched on an FR4 substrate with an overall size of 40 mm × 17 mm × 1.6 mm. The successful implementation of the modified ground plane allows the miniaturization and provides excellent performance. The performance of an antenna shows agreement between both simulation and measurement results.